Giant Spherical Cluster with I‐C140 Fullerene Topology1. Issue 45 (28th September 2015) - Heinl, Sebastian; Peresypkina, Eugenia; Sutter, Jörg; Scheer, Manfred
Abstract: We report on an effective cluster expansion of CuBr‐linked aggregates by the increase of the steric bulk of the Cp R ligand in the pentatopic molecules [Cp R Fe(η 5 ‐P5 )]. Using [Cp BIG Fe(η 5 ‐P5 )] (Cp BIG =C5 (4‐ n BuC6 H4 )5 ), the novel multishell aggregate [Cp BIG Fe(η 5:2:1:1:1:1:1 ‐P5 )12 (CuBr)92 ] is obtained. It shows topological analogy to the theoretically predicted I‐C140 fullerene molecule. The spherical cluster was comprehensively characterized by various methods in solution and in the solid state. Abstract : Change made it possible : The change from Cp* to the sterically highly demanding ligand Cp BIG in the pentaphosphaferrocenes resulted in an effective expansion of the aggregate giant spherical cluster which has a diameter of about 3.5 nm. It exhibits structural analogy to the hitherto unknown I ‐C140 fullerene, a structural motif that has not yet been observed experimentally.